As by fire: The end of the South African university, by Jonathan Jansen - Nkomo, M. (South African Journal of Higher Education, 2019)
Jonathan Jansen’s book, `As by Fire: the end of the South African university’, predicts an apocalyptic spectre, one which will become a reality if it is not immediately confronted and contained. The subtitle evokes an imagery that echoes, though with perhaps less certitude, Francis Fukuyama’s declaration in his `The end of history’, that the demise of communism and the triumph of the free-market liberal democracy system (Fukuyama 1992) should awaken any slumbering citizen and most certainly the government. In all fairness, the book’s subtitle is a warning, rather than the ideologically-inspired pronouncement of Fukuyama. Jansen’s dire prognosis is an inference drawn from the historical downward spiral of many African universities. A rejection of this seeming inevitability might appear to confirm the myth of South Africa’s exceptionalism. In reality, South Africa is not immune to the imperfections afflicting the rest of the pan-African fraternity.